2017
DOI: 10.22495/cocv14i2art7
|View full text |Cite
|
Sign up to set email alerts
|

CEO duality and corporate social responsibility reporting: Evidence from Malaysia

Abstract: This study aims to examine the impact of CEO duality on Corporate Social Responsibility (CSR) reporting by public listed companies in Malaysia. Content analysis was used to determine the extent of CSR reporting. A reporting level index consisting of 51 items was developed based on six themes: General, Community, Environment, Human Resource, Marketplace and Other. In order to determine the relationship between CEO duality and CSR reporting, an Ordinary Least Square regression was employed. The finding of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 100 publications
7
18
0
Order By: Relevance
“…This was in line with our hypothesis, implying that the more power held by the CEO, the lower the level of CSR disclosure. Our findings further validated earlier findings of [Fabrizi,Mallin [66], Ahmad, Rashid [67] who hold that in environments where the legal system is weak and companies are mostly owned and operated by families, the CEOs are entrenched in self-and family-interest and are unlikely to pay much attention to CSR activities and disclosure. Thus, powerful CEOs tend to be less interested in using issues such as CSR to gain legitimacy.…”
Section: Regression Analysis and Discussion Of Resultssupporting
confidence: 91%
“…This was in line with our hypothesis, implying that the more power held by the CEO, the lower the level of CSR disclosure. Our findings further validated earlier findings of [Fabrizi,Mallin [66], Ahmad, Rashid [67] who hold that in environments where the legal system is weak and companies are mostly owned and operated by families, the CEOs are entrenched in self-and family-interest and are unlikely to pay much attention to CSR activities and disclosure. Thus, powerful CEOs tend to be less interested in using issues such as CSR to gain legitimacy.…”
Section: Regression Analysis and Discussion Of Resultssupporting
confidence: 91%
“…This study found that there is a statistical insignificance between CEO duality and SD. This result is in accordance with the findings of Ahmad et al (2017b), Said et al (2009) and Khan et al (2013). Conversely, research was conducted in countries such as the USA (Giannarakis, 2014) and Italy (Allegrini and Greco, 2013) which found a negative significant relationship between CEO duality and SD.…”
Section: Discussionsupporting
confidence: 90%
“…Table 4 also shows negative, but insignificant relationship between the CEO duality and IR, with the correlation coefficient of -0.004 and the significant level of 0.969 which is more than 0.01. This outcome is consistent with the previous study by Ahmad et al (2017) that found no significant association between CEO duality and voluntary disclosure. As family owned companies dominate most of Asian countries business setting, this result is surprising as CEO duality is identical with family owned companies.…”
supporting
confidence: 93%